STRATEGI PUBLIK RELATION DALAM MEMBENTUK CITRA POSITIF DINAS SOSIAL DI KABUPATEN KUDUS - Cahyanti, Nilam; Rohimi, Primi (STAI DI AL-HIKMAH, 2024)
This study aims to find the most effective PR strategy in improving the positive image of the Social Service, P3A Kudus Regency. The research method used is qualitative, producing descriptive data through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions, with data checking using triangulation techniques. The results of the study showed that the PR targets of the Social Service for Women's Empowerment and Child Protection of Kudus Regency were divided into two categories: main targets and specific targets. The main targets include the entire Kudus community, while the specific targets are vulnerable communities, namely those who need assistance from the Social Service and who have limited access to information. The Social Service for Women's Empowerment and Child Protection of Kudus Regency builds a positive image through two approaches: direct and indirect. The indirect approach is carried out by utilizing social media as a tool for disseminating information, both through websites and Instagram. While the direct approach involves Social Service staff in carrying out programs in the community, including socialization, community services, and granting rights and obligations to residents.